Isolation and Identification of Bacteria from Lake Water in and Around Ranipet Area Vellore District - A.Panneerselvam, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Identification of Bacteria from Lake Water in and Around Ranipet Area Vellore District